110k views
1 vote
Find a formula for the sum S of the solutions of the quadratic equation ax²+bx+c=0 .

User Jordin
by
5.3k points

1 Answer

7 votes

Answer:


S = -(b)/(a)

Explanation:

Given a second order polynomial expressed by the following equation:


ax^(2) + bx + c, a\\eq0

This polynomial has roots
x_(1), x_(2) such that
ax^(2) + bx + c = (x - x_(1))*(x - x_(2)), given by the following formulas:


x_(1) = (-b + √(\bigtriangleup))/(2*a)


x_(2) = (-b - √(\bigtriangleup))/(2*a)


\bigtriangleup = b^(2) - 4ac

In this problem, the sum S of the solutions of a quadratic equation is:


S = x_(1) + x_(2)

So


S = (-b + √(\bigtriangleup))/(2*a) + (-b - √(\bigtriangleup))/(2*a)

They have the same denominators, so we can keep the denominators and sum the numerators.


S = (-b + √(\bigtriangleup) - b - √(\bigtriangleup))/(2a)


S = (-2b)/(2a)


S = -(b)/(a)

User Peike
by
5.6k points